Socially Engaged Archive: Art, Media and Public Memory in East Asia - Lu Pan (Media Theory)
Since the 2000s, visual archives related to social movements, activism, community activities, and alternative cultural practices in East Asia have rapidly emerged. This â€œarchival turnâ€ reveals a search for new ways of defining social and communal forms and images beyond official narratives and mass media. In this paper, I use three cases of socially engaged art archival practices â€“ namely, Archive for Human Activities (AHA!), â€œThe Day Afterâ€ and â€œSocially Engaged Art (SEA) CHINAâ€ â€“ to illustrate how artists in East Asia utilize archives as a means of social and individual articulation and conversation. The three cases of archiving practices illustrate new trends in the way archives engage in producing new knowledge and narratives for art and social/cultural practices in East Asia.